Concordance in diabetic foot ulcer infection. Issue 1 (4th January 2013) - Nelson, E Andrea; Backhouse, Michael Ross; Bhogal, Moninder S; Wright-Hughes, Alexandra; Lipsky, Benjamin A; Nixon, Jane; Brown, Sarah; Gray, Janine
Abstract : Introduction: Accurate identification of pathogens, rather than colonising bacteria, is a prerequisite for targeted antibiotic therapy to ensure optimal patient outcome in wounds, such as diabetic foot ulcers. Wound swabs are the easiest and most commonly used sampling technique but most published guidelines recommend instead removal of a tissue sample from the wound bed, which is a more complex process. The aim of this study was to assess the concordance between culture results from wound swabs and tissue samples in patients with suspected diabetic foot infection. Methods and analysis: Patients with a diabetic foot ulcer that is thought to be infected are being recruited from 25 sites across England in a cross-sectional study. The coprimary endpoints for the study are agreement between the two sampling techniques for three microbiological parameters: reported presence of likely isolates identified by the UK Health Protection Agency; resistance of isolates to usual antibiotic agents; and, the number of isolates reported per specimen. Secondary endpoints include appropriateness of the empiric antibiotic therapy prescribed and adverse events. Enrolling 400 patients will provide 80% power to detect a difference of 3% in the reported presence of an organism, assuming organism prevalence of 10%, discordance of 5% and a two-sided test at the 5% level of significance. Assumed overall prevalence is based on relatively uncommon organisms such as Pseudomonas . We will define acceptable agreement as κ>0.6. Ethics and dissemination: Concordance in diabetic foot ulcer infection (CODIFI) will produce robust data to evaluate the two most commonly used sampling techniques employed for patients with a diabetic foot infection. This will help determine whether or not it is important that clinicians take tissue samples rather than swabs in infected ulcers. This study has been approved by the Sheffield NRES Committee (Ref: 11/YH/0078) and all sites have obtained local approvals prior starting recruitment. Study registration: NRES Ref: 11/YH/0078, UKCRN ID: 10440, ISRCTN: 52608451